Role and Risk Factors of Glycosylated Hemoglobin Levels in Early Disease Screening - Guanqun Chao; Yue Zhu; Liying Chen (Journal of Diabetes Research)
Objective. To clarify the correlation among glycosylated hemoglobin (HbA1c), gender, age, fatty liver, and biochemical indicators through the analysis of big database, and to further investigate the risk factors affecting HbA1c, so as to lay a foundation for the study of HbA1c-related diseases and disease management. Methods. People who have been examined in Health Promotion Center from July 2018 to June 2019 were selected as the research objects. All data were analyzed using the Windows R software (version 3.5.1). Detailed medical history inquiry, laboratory examination, and B-ultrasound examination were carried out for the selected sample population. We determined the sample population according to the inclusion and exclusion criteria and, then, further grouped and analyzed the data. T-test or Mann–Whitney U test was used for continuous variable comparison, and chi-square test was used to compare categorical variables. Logistic regression analysis was used to analyze the risk factors of HbA1c. Results. A total of 23,933 subjects were included in this study. The HbA1c level of men was significantly higher than that of women, the HbA1c level of the group with diabetes was higher than that of the group with no diabetes, and the HbA1c level of the group with fatty liver was higher than that of the group with no fatty liver. In the group with no diabetes, the HbA1c level increased with weight gain. Age, gender (male), fatty liver, waist circumference, systolic blood pressure (SBP), triglyceride (TG), blood urea nitrogen (BUN), free thyroxine (FT4), and red blood cell (RBC) were the risk factors for elevated HbA1c level, while high-density lipoprotein cholesterol (HDL-C), uric acid (UA), creatinine (Cr), free triiodothyronine (FT3), and hemoglobin were protective factors. Conclusion. Blood glucose, age, weight, gender, fatty liver, blood lipids, and UA are related to the increase of HbA1c level. HbA1c is related to many metabolic indexes and may be used as a marker for early detection of chronic diseases.